Project "Literacy Room" in Improving Student Scientific Writing Skills at UPN “Veteran” Jawa Timur - Ilmatus Sa’diyah; Eristya Maya Safitri; Anas Ahmadi; Safira Arta; Putri Nur Fadilah Irawan; Fitri Wulandari (Nusantara Science and Technology Proceedings, 2022)
At the university level, the publication of scientific articles is a barometer of the quality of education so students are also required to produce scientific articles that can add to the repertoire of scientific publications. Unfortunately, the increase in capacity and competence in writing scientific articles is mostly intended for lecturers, while for students it is not optimal. Therefore, Indonesian language courses are the first key for students to learn to write scientific articles and learn to publish them in proceedings, book chapters, or journals. One of the learning methods that can be used to improve learning outcomes in writing scientific articles is the project-based learning “Literacy Room”. In particular, this research was conducted using Thiagarajan's 4-P development research method (Definition, Design, Development, and Deployment). The data in this study are student learning outcomes after learning activities using the Literacy Room project-based learning method. Meanwhile, the source of this research data comes from the learning activities of students participating in the general basic Indonesian language course in ten classes, namely class G501, class G511, class G526, class G538, class G521, class G533, class G543, class G546, class G509, and class G552 with a total of 338 students. Data was collected by various data collection methods. First, the data were collected using a questionnaire method with a Likert scale measurement. The resulting data were analyzed using descriptive and inferential analysis through correlation analysis. Based on the research results, the “Literacy Room” project that has been carried out has an impact on improving student's writing skills in quality and quantity.